Evaluation of clinical and pathological response in women with breast cancer undergoing neoadjuvant chemotherapy with docetaxel and doxorubicin: experience of the Lublin centre - Karczmarek-Borowska, Bożenna; Szubstarski, Franciszek (Contemporary Oncology/Współczesna Onkologia, 2004)
Neoadjuvant chemotherapy leads to a significant increase in clinical responses and makes breast-conserving treatment possible. The rate of pathological responses, although generally low, is an important predictive factor of disease-free and overall survival. The aim of the study was to evaluate the clinical and pathological responses after neoadjuvant chemotherapy. Between March and December 2001, 19 patients were assigned to undergo the treatment. The clinical stages of cancers according to the TNM classification were as follows: IIB – 3 patients, IIIA – 15 patients and IIIB – 1 patient. The mean age of patients was 46.6 years. The efficiency according to the WHO was assessed as 0-1. The neoadjuvant treatment included Taxotere 75 mg/m 2 and Doxorubicin 50 mg/m 2 administered during 1 day every 21 days. The number of cycles ranged from 2 (1 patient) to 4. After the treatment the patients were assigned to undergo operative procedures. One patient underwent simple mastectomy, another one-breast-conserving surgery and the remaining women – radical mastectomy. The rate of objective clinical response in 16 patients was 84.2% (cCR 10.5% and cPR 73.7%). Complete pathological response (tumor) was observed in 2 patients (10.5%) while pCR of the lymph nodes in one patient (5.5%). Results: RR did not differ from the data reported by other authors. The value of complete clinical and pathological response of the tumor is similar to the literature data. All the patients are under further clinical observation in order to evaluate distant results (disease-free survival and overall survival).